Suppressed mitochondrial respiration via NOX5-mediated redox imbalance contributes to the antitumor activity of anlotinib in oral squamous cell carcinoma. (20th July 2021) - Huang, Zhexun; Su, Qiao; Li, Wuguo; Ren, Hui; Huang, Huiqiang; Wang, Anxun
Abstract: Anlotinib, a novel multitarget tyrosine kinase inhibitor, has shown promising results in the management of various carcinomas. This study aimed to investigate the antitumor activity of anlotinib in oral squamous cell carcinoma (OSCC) and the underlying molecular mechanism. A retrospective clinical study revealed that anlotinib improved the median progression-free survival (mPFS) and median overall survival (mOS) of patients with recurrent and metastatic (R/M) OSCC, respectively. Functional studies revealed that anlotinib markedly inhibited in vitro proliferation of OSCC cells and impeded in vivo tumor growth of OSCC patient-derived xenograft models. Mechanistically, RNA-sequencing identified that oxidative stress, oxidative phosphorylation and AKT/mTOR signaling were involved in anlotinib-treated OSCC cells. Anlotinib upregulated NADPH oxidase 5 ( NOX5 ) expression, elevated reactive oxygen species (ROS) production, impaired mitochondrial respiration, and promoted apoptosis. Moreover, anlotinb also inhibited phospho- Akt (p-AKT) expression and elevated p-eIF2α expression in OSCC cells. NOX5 knockdown attenuated these inhibitory effects and cytotoxicity in anlotinib-treated OSCC cells. Collectively, we demonstrated that anlotinib monotherapy demonstrated favorable anticancer activity and manageable toxicities in patients with R/M OSCC. The antitumor activity of anlotinib in OSCC may be mainly involved in the suppression of mitochondrial respiration via NOX5-mediated redox imbalance and the AKT/eIF2α pathway.